Can Local Government Mergers Reduce Costs When Capital Expenditures Are Low? Evidence from Court Mergers - Mughan, Sian; Overstreet, Dallin (Urban Affairs Review, 2024)
Local government mergers, motivated by promises of cost savings via economies of scale (EoS) and reduced duplication of function, often fail to produce the anticipated savings. An inability or unwillingness to reduce personnel costs is often offered as a reason for this outcome. We explore this explanation by estimating the expenditure effects of court mergers in California. Our main result is that current judicial spending (total expenditures minus capital expenditures) increases significantly following consolidation. This is partially explained by a sustained increase in salaries paid to full-time workers. The number of workers increases in the years immediately following merger however over the long-term merger has no effect on employment levels, suggesting that mergers change the composition of the workforce. These findings have implications for all local governments that provide labor-intensive services, if mergers are to reduce expenditures officials must be willing to make difficult personnel decisions.
Keywords: Expenditures; Municipal Courts; Synthetic Control; Local Government Consolidation